Insertion of cellulase gene in yeast expression vector (pYY1 and pWYH257 Plasmid) as a candidate for cellulosic ethanol-producing strain - Arief Muammar; Indah Oktaviana; Joseph Chohansandhika; Niken Satuti Nur Handayani (Society for Indonesian Biodiversity, 2021)
Abstract. Muammar A, Oktaviana I, Chohansandhika J, Handayani NSN. 2021. Insertion of cellulase gene in yeast expression vector (pYY1 and pWYH257 Plasmid) as a candidate for cellulosic ethanol-producing strain. Biodiversitas 22: 2715-2721. Production of ethanol from cellulose-based materials often faces obstacles because it requires extensive pretreatment and large amounts of cellulase enzymes. Another method that is more efficient is by inserting cellulase genes from cellulolytic microorganisms such as Aspergillus niger which possess cellulase enzymes encoded by cbhA gene. This gene is inserted into the host which will then be used to produce candidate strains able to produce cellulosic ethanol. This study aimed to insert cbhA gene into vector with a strong promoter to form the candidate. Total RNA was isolated from Aspergillus niger and converted into cDNA. The cbhA gene is amplified from cDNA, then used as insert and inserted into yeast expression vector pYY1 and pWYH257. Vector and inserts were cut using restriction enzymes. Ligation products were transformed into competent cells of Escherichia coli DH10B, the transformation results were confirmed by Colony PCR. Recombinant plasmids were transformed into Saccharomyces cerevisiae INVSc1. The results obtained from the study are that cbhA gene amplification has been successfully carried out by producing DNA bands with the size of 1514 bp as expected for the target gene. The gene was successfully inserted into pYY1 and pWYH257 vector and the recombinant pYY1 plasmid was successfully transformed into Saccharomyces cerevisiae INVSc1